Почти слойная конечность периодической группы без инволюций - Сенашов, В.И. (Український математичний журнал, 1999)
Доведено теорему, що характеризує в класі періодичних груп без інволюцій клас майже шарово скінченних груп: якщо в періодичній спряжено біпримітивно скінченній групі без інволюцій нормалізатор будь-якої нетривіальної скінченної підгрупи майже шарово скінченний, то й сама група майже шарово скінченна. We prove a theorem that characterizes the class of almost layer finite groups in the class of periodic groups without involutions: If the normalizer of any nontrivial finite subgroup of a periodic conjugate biprimitive finite group without involutions is almost layer finite, then the group itself is almost layer finite.